Spiritual intelligence in children within Islamic Educational Psychology: development, potential, and guidance - Nurislamiah, Siti; Setyawati, Ariesta; Astuti, Sherly (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
Spiritual intelligence plays a significant role in Islamic education by bridging the understanding of religious teachings, moral development, and self-awareness regarding the existence of God and humanity. This intelligence involves not only religious knowledge but also values such as empathy, compassion, and a sense of purpose that guide individuals in making ethical decisions and living with integrity. The study emphasizes the importance of spiritual intelligence in fostering well-rounded individuals by integrating intellectual, emotional, and spiritual components. It also highlights the interconnectedness of these aspects, which collectively shape a child’s overall development. The primary objective of this research is to examine the development and potential of spiritual intelligence in children from the perspective of Islamic educational psychology. The study employs a literature review with a qualitative approach, incorporating observations and scientific reasoning to explore this topic. The findings suggest that children's spiritual intelligence can be assessed through their abilities and potential, providing valuable insights into their unique characteristics and developmental needs, which can inform effective educational and parenting strategies. Abstrak Kecerdasan spiritual memainkan peran penting dalam pendidikan Islam dengan menghubungkan pemahaman ajaran agama, perkembangan moral, dan kesadaran diri terkait eksistensi Tuhan dan umat manusia. Kecerdasan ini melibatkan tidak hanya pengetahuan agama, tetapi juga nilai-nilai seperti empati, kasih sayang, dan rasa tujuan hidup yang membimbing individu dalam mengambil keputusan etis dan hidup dengan integritas. Studi ini menekankan pentingnya kecerdasan spiritual dalam membentuk individu yang seimbang dengan mengintegrasikan komponen intelektual, emosional, dan spiritual. Hal ini juga menyoroti keterkaitan antara ketiga aspek tersebut, yang secara kolektif membentuk perkembangan anak secara keseluruhan. Tujuan utama dari penelitian ini adalah untuk memeriksa perkembangan dan potensi kecerdasan spiritual pada anak-anak dari perspektif psikologi pendidikan Islam. Penelitian ini menggunakan tinjauan pustaka dengan pendekatan kualitatif, yang mencakup pengamatan dan penalaran ilmiah untuk menggali topik ini. Hasil penelitian menunjukkan bahwa kecerdasan spiritual anak dapat diukur melalui kemampuan dan potensi mereka, yang memberikan wawasan berharga mengenai karakteristik unik dan kebutuhan perkembangan mereka, yang dapat menjadi dasar bagi strategi pendidikan dan pengasuhan yang efektif.